The Effect of Crew Manning Services and Crew Placement on Human Resource Quality: The Mediating Role of Crew Competence at PT Augustea Intcrews Indonesia - Nadifa Salsabila Hadiwinoto; Renanda Aurelia Putri; April Gunawan; Imam Fahcruddin; Vidya Selasdini (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The main problem in this study is the suboptimal quality of human resources at PT Augustea Intcrews Indonesia, which is indicated by variations in the quality of crew manning services, the accuracy of crew placement, and differences in crew competency levels in meeting shipping operational needs. These conditions potentially affect the professionalism and performance of human resources amid increasing demands in the maritime industry and dynamic regulatory changes. This study aims to analyze the influence of crew manning services and crew placement on crew competency and their impact on qualified human resources. The study employed a quantitative approach using a survey method. The research population consisted of service users and related parties at PT Augustea Intcrews Indonesia, with a sample of 115 respondents selected through purposive sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results showed that crew manning services and crew placement have a positive and significant effect on crew competency and qualified human resources. Crew competency was also proven to have a significant effect on the quality of human resources and to mediate the relationship between crew manning services and crew placement on qualified human resources. The study concludes that improving the quality of crew manning services, ensuring appropriate crew placement, and continuously developing crew competencies are the main factors in creating professional and qualified maritime human resources. Therefore, the company is recommended to strengthen its training systems, certification management, and competency-based crew placement to support the sustainable improvement of human resource quality.